Implementation of Electronic Medical Records System EQUALI to Improve Patient Care - Tula Espinoza-Cordero; Katherin Ortiz-Cotrina; Carlos Carranza-Llanos; Juan Carlos Cotrina-Aliaga (Indonesian Scientific Journal, 2021)
In the present, where we live a pandemic because of Covid-19, it presents a challenge and change in the way we live for all, in which a different way of being able to receive health care must be created. in this research aimed to implement the electronic medical records system to improve patient care, such research is descriptive-explanatory in which a population of 67 patients from a health center is sampled. In conclusion, the implementation of the Electronic Medical Records System improved patient administrative care at the Health Center.